Three Houses that are Three Ideas - Alberto Campo Baeza (Oz, 2003)
I will not tire of repeating that architecture without ideas to sustain it is nothing: it is only form, and forms pass with time and are destroyed. An idea, a constructed idea, reveals itself, unveils in its entirety when it is materialized, constructed: when it is a constructed idea.